Optimasi Port Knocking dan Honeypot Menggunakan IPTables Sebagai Keamanan Jaringan pada Server - Yayank Muhammad Abdussyakur; Ahmad Zafrullah Mardiansyah; Andy Hidayat Jatmika (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2021)
Network security is the most important aspect of a system in maintaining data validation and integrity, as well as ensuring the availability of services for its users. The development of network security system demands a better security, especially in servers. However, there are still weaknesses in the server that controls incoming packet which results in more vulnerable it is to be stormed by Denial of Service and Brute Force attacks on the system. This study aims to improve network security performance using the Port Knocking and Honeypot methods which will be combined with the Iptables method. From the tests carried out with the addition of the IPTables method, an increase in performance of CPU usage (38.4%) and memory (44.2%) on servers and network security were obtained compared to those that only use the Port Knocking and Honeypot methods.